PENGGUNAAN MEDIA AUDIOVISUAL UNTUK MENINGKATKAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN MEMBIAKAN TANAMAN DENGAN BIJI JURUSAN AGRIBISNIS PEMBIBITAN DAN KULTUR JARINGAN KELAS X DI SMK NEGERI 4 JENEPONTO - Indha Nurul Fauziah G; Muhammad Rais; Jamaluddin P Jamaluddin P (Jurnal Pendidikan Teknologi Pertanian, 2017)
The goal of this research is to improve plant breeding learning activities using audiovisual media to improve the learning outcomes of students studying plant breeding with seeds using audiovisual media. The method used for this research is classroom action research. Data are acquired through observations, interviews and research questionnaire. Technique of data analysis used is descriptive quantitative and qualitative. The use of audiovisual media spurs students to be more enthusiastic during lessons because audiovisual media has an appealing factor in that it uses real pictures that can be seen and heard. The results of this research shows that using the audiovisual leeson model has a significant contribution in increasing activeness in learning and learning achievement. This shows  that audiovisual media learning can be used while learning because the learners’ target has been reached according to the criterion.